Synergistic consequences of early-life social isolation and chronic stress impact coping and neural mechanisms underlying male prairie vole susceptibility and resilience - Sailer, Lindsay L.; Patel, Pooja P.; Park, Ashley H.; Moon, Joanna; Hanadari-Levy, Amit; Ophir, Alexander G. (Frontiers in Behavioral Neuroscience, 2022)
Chronic stress can be challenging, lead to maladaptive coping strategies, and cause negative mental and physical health outcomes. Early-life adversity exposes developing young to physical or psychological experiences that risks surpassing their capacity to effectively cope, thereby impacting their lifetime physical and mental wellbeing. Sensitivity to stressful events, like social isolation, has the potential to magnify stress-coping. Chronic stress through social defeat is an established paradigm that models adverse early-life experiences and can trigger enduring alterations in behavioral and neural phenotypes. To assess the degree to which stress resilience and sensitivity stemming from early-life chronic stress impacts sociability, we exposed male prairie voles to chronic social defeat stress (CSDS) during adolescence. We simultaneously exposed subjects to either social isolation (CSDS+Isol) or group housing (CSDS+Soc) during this crucial time of development. On PND41, all subjects underwent a social approach test to examine the immediate impact of isolation, CSDS, or their combined effects on sociability. Unlike the CSDS+Isol group that primarily displayed social avoidance, the CSDS+Soc group was split by individuals exhibiting susceptible or resilient stress phenotypes. Notably, the Control+Soc and CSDS+Soc animals and their cage-mates significantly gained body weight between PND31 and PND40, whereas the Control+Isol and CSDS+Isol animals did not. These results suggest that the effects of early life stress may be mitigated by having access to social support. Vasopressin, oxytocin, and opioids and their receptors (avpr1a, oxtr, oprk1, oprm1, and oprd1) are known to modulate social and stress-coping behaviors in the lateral septum (LS). Therefore, we did an mRNA expression analysis with RT-qPCR of the avpr1a, oxtr, oprk1, oprm1, and oprd1 genes to show that isolation and CSDS, or their collective influence, can potentially differentially bias sensitivity of the LS to early-life stressors. Collectively, our study supports the impact and dimensionality of early-life adversity because the type (isolation vs CSDS), duration (acute vs chronic), and combination (isolation + CSDS) of stressors can dynamically alter behavioral and neural outcomes.